El sonido neo psicodélico: Producción de dos temas inéditos, a partir del análisis de producción de dos temas del disco Lonerism de Tame Impala - Gándara Yépez, Juan Sebastián (2021)
In this project, the production of two unreleased psychedelic rock songs will be carried out. The focus of the project is centered on music production. For this process the songs will go through three stages: recording, mixing and mastering…